Effectiveness of Beauveria bassiana and three selected botanicals on controlling Idioscopus clypealis and increasing mango fruit set and fruit retention - Rahman, Md. Sohanur; Jahan, Mahbuba; Rahman, Md. Arifur (Journal of the Bangladesh Agricultural University, 2020)
This study was carried out to study the effects of a microbial pesticides (Beauveria bassiana) and three botanicals (Neem, Mahogany and Karanja oils) for the management of mango hopper (Idioscopus clypealis) to increase the fruit set and retention of mango. The experiment was conducted mat Aqua, Mymensingh, Bangladesh following randomized complete block design (RCBD). Each of the botanicals and microbial pesticides was used with 3 different doses (1%, 2% and 3%). The observation on fruit set after pesticides application showed that the highest percentage of fruit setting was found in 1% Beauveria bassiana (8.33%) that was statistically similar to 2% Beauveria bassiana and the lowest number of fruit setting (3.6%) was found in 1% Mahogany oil. Among the botanicals, 3% neem oil (11.46%) had better performance on fruit setting. Observation on fruit retention after pesticides application showed that the percentage of fruit retention was maximum (10.50%) in 1% Beauveria bassiana and the lowest (4.86%) was found in 1% Mahogany oil. Among botanicals, 3% neem oil (8.07%) had better performance on fruit retention. Overall results suggested that Beauveria bassiana as a microbial pesticide performed better than botanicals for the mango fruit set and retention and it can be used as a promising microbial pesticide to ensure the quality mango production. J Bangladesh Agril Univ 18(2): 367–372, 2020 https://doi.org/10.5455/JBAU.75456